2016
DOI: 10.1039/c5nr08943c
|View full text |Cite
|
Sign up to set email alerts
|

Bisulfite induced chemiluminescence of g-C3N4nanosheets and enhanced by metal ions

Abstract: In this work, a novel chemiluminescence (CL) phenomenon was found: a g-C3N4 nanosheets suspension was mixed with NaHSO3 solution directly to produce luminescence, and the intensity of luminescence could be obviously enhanced by some metal ions, which was distinctly different from the phenomenon that Cu(2+) ions can quench the fluorescence of g-C3N4 nanosheets as reported before.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…In addition, it has been demonstrated that reduced-sized GCNNs and GCN quantum dots with much smaller lateral dimension can be used for bio-imaging due to their distinct fluorescence with low photo-bleaching and low cytotoxicity [21]. However, multilayer GCNNs reported so far have a low fluorescence quantum yield (less than 20%) [8,9,22], and GCN quantum dots show ignorable photocatalytic activity under visible light irradiation [23]. It is believed that nanosized monolayer graphitic carbon nitride nanosheets (NMGCNs) would be highly photo-responsive for both photocatalysis and fluorescence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been demonstrated that reduced-sized GCNNs and GCN quantum dots with much smaller lateral dimension can be used for bio-imaging due to their distinct fluorescence with low photo-bleaching and low cytotoxicity [21]. However, multilayer GCNNs reported so far have a low fluorescence quantum yield (less than 20%) [8,9,22], and GCN quantum dots show ignorable photocatalytic activity under visible light irradiation [23]. It is believed that nanosized monolayer graphitic carbon nitride nanosheets (NMGCNs) would be highly photo-responsive for both photocatalysis and fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fascinating physicochemical and electronic properties arising from the small dimensions and quantum confinement effects (QCE) [1][2][3], ultrathin nanosheets have been the focus of substantial research in the light of fundamental studies and their broad applications in various fields, including optoelectronic devices [4], energy conversion and storage [5], sensors [6][7][8][9], biomedicine [10], and catalysis [11][12][13][14][15]. In particular, polymeric graphitic carbon nitride nanosheets (GCNNs), an n-type semiconductor, have been receiving considerable attention due to their many intriguing advantages such as the fact that they contain no metal, and nontoxicity, easy availability, sensitive photo-response, excellent chemical and thermal stability, and unique electronic structures [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al found that ZnS quantum dots could enhance the chemiluminescence of the NaHSO 3 –H 2 O 2 system and the mechanism in an acidic medium has been studied in detail . They also found that the chemiluminescence of NaHSO 3 can be catalyzed by g‐C 3 N 4 nanosheets and the intensity of luminescence could be obviously enhanced by some metalions …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Lin's group observed a novel chemiluminescence phenomenon when g-C 3 N 4 nanosheet suspension was mixed with NaHSO 3 solution [70], and the intensity of CL could be obviously enhanced by some metal ions (Cu 2? , Fe 3? or Mn 2?…”
Section: Graphitic Carbon Nitride As Catalyst In CL Systemsmentioning
confidence: 99%
“…-NaHSO 3 system. Reprinted with permission [70] a-Fe 2 O 3 /g-C 3 N 4 composites, strong CTL emission would generate with fast response and short recovery time approximatively 0.1 and 0.6 s, respectively, based on which a highly sensitive H 2 S gas sensor was developed. It can be concluded from the experimental results that the introduction of g-C 3 N 4 into the composite played a key role in enhancing CTL-sensing performance for H 2 S and reducing the CTL reaction temperature.…”
Section: Cataluminescencementioning
confidence: 99%